ФОРМУВАННЯ ЦІННІСНОЇ ОРІЄНТАЦІЇ СТУДЕНТІВ ПЕДАГОГІЧНОЇ ШКОЛИ ЯК УМОВА ЇХ ПРОФЕСІЙНОЇ КОМПЕТЕНТНОСТІ (Педагогіка вищої та середньої школи, 2008)
The article deals with some problems of value orientations in students’ life. The analysis of value orientations in students' life in higher educational establishments of economy and pedagogy is provided.